Is there a Role for Preoperative Infusion or Intraoperative Cholangiography?. Issue 5 (1997) - Lau, W. Y.; Li, Arthur K. C.
Abstract : Background : There has been a resurgence of interest in recent years in preoperative infusion cholangiography (PIC). The role of routine PIC compared to routine intraoperative cholangiography (IOC) has not been clearly defined. Study design : In our department between 1985 and 1991, 1, 042 of 1, 576 consecutive patients with biliary calculous disease had elective cholecystectomy: 694 patients were prospectively scheduled for PIC, and 348 patients were randomly allocated to IOC. The patients in the PIC and IOC groups were similar with regard to age, history of biliopancreatic complications, and laboratory findings. The cost of PIC in Sweden is nearly five times greater than the cost of IOC. Results : Satisfactory opacification of the biliary system was obtained in 90.1 and 96.8 percent of patients who underwent PIC and IOC, respectively. Preoperative infusion cholangiography required support by IOC in 19.5 percent of patients. There were no statistically significant differences between the PIC and IOC groups with regard to the incidence (7 percent in both groups) of or positive predictive value (68 and 80 percent, respectively) for bile duct stones, rate of retained stones (6 and 20 percent, respectively), intraoperative (5.6 and 6.3 percent, respectively) or postoperative (13.3 and 15.9 percent, respectively) morbidity, or incidence of bile duct anomalies (0.9 and 0.3 percent, respectively). Median operative time was longer in .patients with (95 minutes) compared to those without (75 minutes) IOC ( p <0.001). More postoperative complications occurred after bile duct exploration (26 of 75 patients) compared to cholecystectomy alone (114 of 917 patients, p <0.001). The 30-day mortality was zero. Minor bile duct injuries occurred in two patients (0.2 percent) at cholecystectomy, (one with and one without bile duct exploration). In no patient was the cholangiographic finding of a biliary anomaly crucial for the safe execution of cholecystectomy. Conclusions : In our study, PIC and IOC were comparable, but routine use of either method did not promote the safety of cholecystectomy and thus their routine use is not warranted. The shorter operative time and preoperative identification of common bile duct (CBD) stones provided by PIC might favor this examination when applied selectively in patients with increased risk of having CBD stones. However, this potential advantage is offset by the need for PIC to be supported by IOC in approximately 20 percent of patients. Also, the cost of PIC is greater than the cost of IOC.